2020
DOI: 10.1111/acem.13998
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Costs and Reimbursement Model for a Geriatric Emergency Department

Abstract: Objectives: The American College of Emergency Physicians' geriatric emergency department (GED) guidelines recommend additional staff and geriatric equipment, which may not be financially feasible for every ED. Data from an accredited Level 1 GED was used to report equipment costs and to develop a business model for financial sustainability of a GED. Methods: Staff salaries including the cost of fringe benefits were obtained from a Midwestern hospital with an academic ED of 80,000 annual visits. Reimbursement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The 106‐bed academic, tertiary referral hospital ED includes a 15‐bed oncology area with oncology‐trained ED nurses and a 20‐bed Observation Unit area. It is an accredited Level 1 geriatric ED 16 …”
Section: Methodsmentioning
confidence: 99%
“…The 106‐bed academic, tertiary referral hospital ED includes a 15‐bed oncology area with oncology‐trained ED nurses and a 20‐bed Observation Unit area. It is an accredited Level 1 geriatric ED 16 …”
Section: Methodsmentioning
confidence: 99%
“…Physical therapists can bill for their ED evaluations, 49 and medication therapy management by pharmacists is covered by Medicare for patients with polypharmacy (receiving 5 or more medications). Southerland et al 50 evaluated the financial feasibility of multidisciplinary consultations in the ED and found that per workday a pharmacist is financially self-sustaining at 7.7 medication reconciliation consultations and a physical therapy is self-sustaining at 5.7 consultations. An average fall-related ED visit costs Medicare $5,000 to $6,000.…”
Section: Discussionmentioning
confidence: 99%
“…Jesse M. Pines, MD, MBA 1,2 (pinesj@usacs.com) Simon Edginton, MD 1 Amer Z. Aldeen, MD 1 1 US Acute Care Solutions, Canton, OH, 2 Department of Emergency Medicine, Allegheny General Hospital, Pittsburgh, PA,…”
mentioning
confidence: 99%
“…In this issue of Academic Emergency Medicine , Southerland et al 1 describe a business model for staffing and equipment in a Level 1 accredited, academic geriatric emergency department (GED). The authors described program costs, including staff salaries for a geriatric nurse practitioner, pharmacist, and physical and occupational therapists.…”
mentioning
confidence: 99%